2015
DOI: 10.1007/s12550-015-0236-4
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to aflatoxin B1 in Thailand by consumption of brown and color rice

Abstract: This study assessed the aflatoxin B1 (AFB1) intake of the Thai population through consumption of contaminated brown and color rice. A total of 240 rice samples from two harvesting periods were collected in June/July 2012 (period I) and in December 2012/January 2013 (period II) and analyzed for AFB1 by HPLC with fluorescence detection (limit of detection (LOD) = 0.093 ng/g). Exposure assessment was based on AFB1 levels in rice and food intake data for rice according to Thai National Consumption. Frequency and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 15 publications
2
19
0
Order By: Relevance
“…Based on these results, it is obvious that the intake of contaminated rice is of great public health concern. Our results for the estimated cancer risk and MoE due to AFB 1 intake by rice consumption are comparable with those of previous studies reported for Japan [ 67 ] and Thailand [ 40 ]. The study for Japan measured a cancer risk of 0.031 cancer/year/10 5 , and a MoE of 141 for children (age 7–14 years) resulting from AFB 1 intake by rice consumption, while in adults the values of cancer risk and margin of exposure were 0.021 cancer/year/10 5 and 209 MoE, respectively [ 67 ].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Based on these results, it is obvious that the intake of contaminated rice is of great public health concern. Our results for the estimated cancer risk and MoE due to AFB 1 intake by rice consumption are comparable with those of previous studies reported for Japan [ 67 ] and Thailand [ 40 ]. The study for Japan measured a cancer risk of 0.031 cancer/year/10 5 , and a MoE of 141 for children (age 7–14 years) resulting from AFB 1 intake by rice consumption, while in adults the values of cancer risk and margin of exposure were 0.021 cancer/year/10 5 and 209 MoE, respectively [ 67 ].…”
Section: Discussionsupporting
confidence: 91%
“…Because of the low contamination levels, the dietary exposures to AFB 1 from rice and wheat intake in French adults (<LOD—0.018 ng/kg b.w./day) and children (<LOD—0.035 ng/kg b.w./day) [ 38 ], as well as in the Lebanese population (0.63–0.66 ng/kg b.w/ day) based on total diet intake were lower than those observe in the present study [ 68 ]. The current data is higher than the reported mean dietary exposure to AFB 1 (0.8 and 0.12 ng/kg b.w./day) by rice consumption in Thailand in the years 2012 and 2013 [ 40 ]. Also, the dietary exposure to AFB 1 (0.033 ng/kg b.w./day) in Morocco [ 44 ] and that to total AFs in French adults (0.014 ng/kg b.w./day) and children (0.077 ng/kg b.w./day) [ 39 ] are lower than those observed in the current study.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations